Expanding the Myxochelin Natural Product Family by Nicotinic Acid Containing Congeners - Nicolas A. Frank; Márió Széles; Sergi H. Akone; Sari Rasheed; Stephan Hüttel; Simon Frewert; Mostafa M. Hamed; Jennifer Herrmann; Sören M. M. Schuler; Anna K. H. Hirsch; Rolf Müller (Molecules, 2021)
Myxobacteria represent a viable source of chemically diverse and biologically active secondary metabolites. The myxochelins are a well-studied family of catecholate-type siderophores produced by various myxobacterial strains. Here, we report the discovery, isolation, and structure elucidation of three new myxochelins N1–N3 from the terrestrial myxobacterium Corallococcus sp. MCy9049, featuring an unusual nicotinic acid moiety. Precursor-directed biosynthesis (PDB) experiments and total synthesis were performed in order to confirm structures, improve access to pure compounds for bioactivity testing, and to devise a biosynthesis proposal. The combined evaluation of metabolome and genome data covering myxobacteria supports the notion that the new myxochelin congeners reported here are in fact frequent side products of the known myxochelin A biosynthetic pathway in myxobacteria.